Analisis Tindak Tutur Caption dalam Instagram Ridwan Kamil - Ai Azizah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This reseacrh is motivated by the phenomenon of speech which give effect to the speaker. The source of the utterance is derived from the instagram account Mr. Ridwan Kamil. Social media instagram has benefits as a means of providing information, messange, expression, and news. Through this research, the researcher will examine or fornulate speech caption contained in the instagram Ridwan Kamil. As this study aims to determine the type of speech act the caption contained in the accunt instagram Ridwan Kamil. Thype-the type of speech act is described by the reseacrhers. In addition, the reseacrher also aims to describe the intention of illocutionary speech acts which include the assertive, directive, expressive, commissive and declarative. The subject of this research is speech caption  in the account instagram Ridwan Kamil. The object of this research is the forms of illocutionary speech acts (assertives, directives, expressives, commissive and declarative) that are contained in the type of speech act. This research instument is the researcher himself by using documentation technique and technique select. Data collection techniques using select and documentation techniques. Data analysis used qualitative method. The results of the data described by the reseacrhes. Based on the results of the study concluded that in the caption accounts instagram Ridwan Kamil, there are speech acts of directive (commanding), illocutionary expressive (thank you), the illouctionary directive (giving advice), the illocutionary assertive (shows), and the illocutionary commissive (offer).